Pengaruh Sikap Kerja dan Motivasi Kerja terhadap Kinerja Pegawai di Bidang Hukum Kepolisian Daerah (Polda) Sumatera Utara - Jenni Theresia Tampubolon; Bakhtiar Bakhtiar; Julkarnain Julkarnain (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The formulation of this research is how the influence of Work Attitude and Work Motivation on Employee Performance in the Legal Field of the North Sumatra Regional Police (POLDA). The purpose of this study was to determine and analyze work attitudes and work motivation towards employee performance in the legal field of the North Sumatra Regional Police (POLDA). This research is quantitative descriptive research. Data collection techniques are done through interviews, questionnaires and documentation studies. The sample in this study were 37 employees. Variables are measured with a Likert scale. Hypothesis testing using multiple linear regression analysis through the F test and t test. The test results simultaneously show that work attitude and work motivation have a significant effect on employee performance variables in the Legal Division of the North Sumatra Regional Police (POLDA) with a coefficient of determination of 1%. Partially, work discipline has a positive and significant effect on employee performance in the Legal Division of the North Sumatra Regional Police (POLDA) with a regression coefficient value of 1%, work motivation has a positive and significant effect on employee performance in the Legal Division of the North Sumatra Regional Police (POLDA) with a regression coefficient value of 1 %. The highest regression coefficient value is work motivation.